Effects of Tirofiban on Random Skin Flap Survival in Rats - Cheng, Liang; Chen, Tingxiang; Li, Hang; Feng, Zhenghua; Li, Zhijie; Lin, Dingsheng (Journal of Reconstructive Microsurgery, 2018)
Background Tirofiban is a glycoprotein IIb/IIIa receptor antagonist that is widely used clinically. In the present study, we investigated whether tirofiban promotes flap survival in rat random skin flap model.Methods “McFarlane flaps” models were developed in 60 male rats. The rats were divided into a tirofiban-treated group (n = 30) and a saline-treated group (n = 30). The flap surviving rate was calculated 7 days after surgery. Tissue samples were collected and subjected to histopathological evaluation. Lead oxide–gelatin angiography and immunohistochemical staining analysis were taken to evaluate angiogenesis. Analysis of oxidative stress was performed by measuring the activity of superoxide dismutase (SOD) and malondialdehyde (MDA).Results Compared with controls, the tirofiban-treated groups exhibited significantly larger mean areas of flap survival, significantly increased SOD activity, and vascular endothelial growth factor (VEGF) expression, and significantly reduced MDA level. Hematoxylin and eosin staining revealed that naringin promoted angiogenesis and inhibited inflammation.Conclusion These findings demonstrate that tirofiban increases flap survival of random skin flaps in rats.
Keywords: tirofiban; random skin flap; flap survival